The Effect of Depths of Partial Breakwater on Wave Transmissibility by Physical Model - อินทรียงค์ นันทวุฒิ; Sriariyawat, Anuruk (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
Coastal erosion in Thailand becomes more dangerous nowadays, especially in the Upper Gulf of Thailand, where is the mudflat. Some kinds of mitigation structures face the subsidence problem because of the lack of the strength capacity of the muddy ground. Therefore, not every type of protection structure can be constructed on this clay. Only the structure that transfers its weight directly and deeply into the ground can initiate in this muddy area. In Khun Samut China village located in Samut Prakan province, the villagers applied the piles with the partial wall on the water surface, as called “partial breakwater”, to protect their land. This kind of structure is an appropriate alternative and has a higher potential for muddy coast protection. However, the effectiveness of the partial breakwater was studied only from the influence of the wave characteristics. The impact of the appearance of the structure is not yet proved. This study aims to investigate the relationship between the physical attributes of the breakwater and the transmission ability of waves through it. The experiment was conducted by varying the depth of the partial breakwater and measuring wave height before and after it hit the structure. After that, the transmission coefficient was calculated. Besides, the influence distance after the structure was considered. The results showed that the more structure depth is, the less wave transmission coefficient becomes. In conclusion, the inverse variation is the tread of the relationship between these two parameters. The results of the study will be usefully revealed to support the design of the mitigation structure for the erosion problem of the muddy coast in the future.